Haemodynamic and End Tidal CO2 Changes State after Inflation and Deflation of Pneumatic Tourniquet on Extremities (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):524-8The abstract of this article is available on the PubMed website